2021
DOI: 10.1002/advs.202101374
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Omics Analysis Reveals the Mechanism Underlying the Edaphic Adaptation in Wild Barley at Evolution Slope (Tabigha)

Abstract: At the microsite "Evolution Slope", Tabigha, Israel, wild barley (Hordeum spontaneum) populations adapted to dry Terra Rossa soil, and its derivative abutting wild barley population adapted to moist and fungi-rich Basalt soil. However, the mechanisms underlying the edaphic adaptation remain elusive. Accordingly, whole genome bisulfite sequencing, RNA-sequencing, and metabolome analysis are performed on ten wild barley accessions inhabiting Terra Rossa and Basalt soil. A total of 121 433 differentially methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 75 publications
(116 reference statements)
5
20
0
Order By: Relevance
“…Compared with unexpressed genes, CG gene body methylation levels of expressed genes were higher than those of unexpressed genes, whereas non-CG methylation was lower in expressed gene body regions than that in unexpressed genes. Consistent with previous studies (Cai et al, 2021;Xu et al, 2018), DNA methylation levels at the transcription start site (TSS) and transcription end site (TES) were significantly reduced in expressed genes compared with those in unexpressed genes. Additionally, a significant increase in CHH promoter methylation was observed in the expressed genes.…”
Section: The Association Between Dna Methylation and Gene Activitysupporting
confidence: 89%
See 4 more Smart Citations
“…Compared with unexpressed genes, CG gene body methylation levels of expressed genes were higher than those of unexpressed genes, whereas non-CG methylation was lower in expressed gene body regions than that in unexpressed genes. Consistent with previous studies (Cai et al, 2021;Xu et al, 2018), DNA methylation levels at the transcription start site (TSS) and transcription end site (TES) were significantly reduced in expressed genes compared with those in unexpressed genes. Additionally, a significant increase in CHH promoter methylation was observed in the expressed genes.…”
Section: The Association Between Dna Methylation and Gene Activitysupporting
confidence: 89%
“…Wang et al, 2015;Xu et al, 2018;. CG methylation of gene body regions is always positively correlated with gene expression (Cai et al, 2021;H. Wang et al, 2015;Xu et al, 2018), but we observed that the highest-expressed genes did not have the highest CG methylation levels in the gene body (Figures 4 and S11).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations